1987
DOI: 10.1172/jci113213
|View full text |Cite
|
Sign up to set email alerts
|

Effects of potassium on ammonia transport by medullary thick ascending limb of the rat.

Abstract: Renal ammonium excretion is increased by potassium depletion and reduced by potassium loading. To determine whether changes in potassium concentration would alter ammonia transport in the medullary thick ascending limb (MAL), tubules from rats were perfused in vitro and effects of changes in K concentration within the physiological range (4-24 mM) were evaluated. Increasing K concentration from 4 to 24 mM in perfusate and bath inhibited total ammonia absorption by 50% and reduced the steady-state transepitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…Good has suggested that changes in luminal potassium concentration in the physiologic range may modulate ammonium transport in the thick ascending limb such that high luminal potassium concentrations inhibit ammonium ion reabsorption in this segment, thereby reducing the accumulation of total ammonia in the medulla (16). In the present study, high luminal potassium concentrations in proximal tubule segments stimulated net secretion of total ammonia into the lumen.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Good has suggested that changes in luminal potassium concentration in the physiologic range may modulate ammonium transport in the thick ascending limb such that high luminal potassium concentrations inhibit ammonium ion reabsorption in this segment, thereby reducing the accumulation of total ammonia in the medulla (16). In the present study, high luminal potassium concentrations in proximal tubule segments stimulated net secretion of total ammonia into the lumen.…”
Section: Discussionsupporting
confidence: 55%
“…In fact, ammonium ions may be transported instead of potassium ion on the Na'-K' ATPase of the proximal tubule (14,15), and probably on the NaKCI cotransporter in the thick ascending limb of Henle (16). The present studies in isolated mouse proximal tubules demonstrate the influence of ambient K+ concentration on net luminal secretion of ammonia.…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, they have been shown to interact with H + -K + -ATPase and influence its activity in the rabbit gastric mucosa (16). However, the slight changes in blood K + concentrations at baseline and upon acid loading (SI Appendix, Tables S1 and S2) were unlikely to affect renal acid-base handling in mutant mice (37,38). Concomitantly, ammoniagenesis in isolated proximal tubular segments of double-mutant cortices was similar to controls.…”
Section: Discussionmentioning
confidence: 96%
“…2 Therefore, both mechanisms of RTA type 4 work together to inhibit the excretion of NH3 into the collecting duct of the kidney and subsequently inhibit the excretion of NH4+ and an acid load.…”
Section: A 67 Year-old Man With Fatiguementioning
confidence: 99%